WOMEN’S KNOWLEDGE, ATTITUDE AND PRACTICE TOWARDS MENOPAUSE AND HORMONE REPLACEMENT THERAPY: A FACILITY BASED STUDY IN AL-AIN, UNITED ARAB EMIRATES - Hamid, Saima; Al-Ghufli, Fatma Rashid; Raeesi, Hanan Ali; Al-Dhufairi, Khawla Mohammed; Al-Dhaheri, Noura Salem; Al-Maskari, Fatma; Blair, Iain; Shah, Syed Mahboob (Journal of Ayub Medical College Abbottabad, 2014)
Background: Hormone replacement therapy (HRT) is an effective treatment for menopausal symptoms like vasomotor symptoms, sleep disturbances, mood alteration, depression, urinary tract infection, vaginal atrophy and increased health risks for osteoporosis, cardiovascular diseases and loss of cognitive function. This study was conducted to determine knowledge, attitude and practice toward menopause among women in UAE. Methods: A clinic-based cross-sectional study was carried out among women of age 40 and above. Study subjects were recruited from four Primary Health Care centres in Al Ain city. The participants were administered a questionnaire in Arabic and English, which included 33 items; socio-demographic variables, and questions related to knowledge, attitude and practices regarding menopause and HRT. Results: Out of 177 study subjected selected, 150 (85%) completed the survey. Almost half of the participants (51%) had already experienced menopause. A substantial number of women had poor know knowledge about menopause (67%) and HRT (73%). Sixty percent of women had positive attitude towards menopause. Of the fifty three percent of women with symptoms, 35% of them did not use anything to relieve their symptoms. Knowledge about menopause varied significantly (p<0.05) with the level of education and nationality. The association between reported symptoms and attitude towards menopause and HRT was found to be statistically significant. Women with reported symptoms that were bothersome had positive attitude towards HRT uptake. Conclusion: The study indicated that there is poor knowledge about menopause and HRT among the participants. Level of knowledge was associated with the level of education. There was a positive attitude towards menopause, with women suffering the most from menopausal symptoms showing positive attitude towards HRT. Keywords: HRT, Menopause, UAE